Comparative Analysis of Microbial Load of the Main Water Production and Water Availability in Federal University Wukari - Umaru, Isaac John; Asare, Solomon Ossom; Omanchi, Emmanuel; Olayemi, Abimbola Gbenga; Morgan, Akpan Usenobong (Darul Yasin Al Sys, 2025)
Access to clean and safe water is a critical component of public health and institutional sustainability, particularly in academic environments where large populations depend on reliable water sources for daily activities. Federal University Wukari, located in Taraba State, Nigeria, primarily relies on boreholes and hand-dug wells to meet its water needs; however, these sources are susceptible to microbial contamination due to poor construction, proximity to waste disposal sites, and seasonal fluctuations in groundwater levels. This study conducted a comparative analysis of the microbial load in water samples collected from boreholes and wells across various campus locations. Standard microbiological techniques were employed to quantify total heterotrophic bacteria, coliforms, and the presence of Escherichia coli, and a structured survey was administered to assess water availability and usage patterns among students and staff. Results revealed that well water samples consistently exhibited higher microbial loads, with E. coli detected in all well sources, whereas borehole samples showed significantly lower contamination levels, and statistical analysis confirmed a significant difference in microbial counts between the two water sources (p < 0.05). The survey further indicated disparities in water availability, with student hostels and off-campus staff areas experiencing the most frequent shortages. These findings underscore the urgent need for routine water quality monitoring, infrastructural improvements, and policy interventions to ensure safe and equitable water access within the university. The study contributes to the broader discourse on water safety in Nigerian tertiary institutions and provides actionable insights for campus health and infrastructure planning.